Nanomedicine in cardiovascular and cerebrovascular diseases: targeted nanozyme therapies and their clinical potential and current challenges - Yanhua Jiang; Yongjian Zhou; Zhe Li; Liang Guo (Journal of Nanobiotechnology)
Abstract Cardiovascular and cerebrovascular diseases continue to be significant public health problems, with high mortality and morbidity rates worldwide. Inflammation and ROS are believed to be the hallmarks of these diseases, but conventional therapies targeting inflammation and ROS have had limited success due to their limited pharmacokinetics, low bioavailability, shorter half-life, and notable side effects. Over the last decade, nanomedicine has rapidly evolved with diverse applications in diagnostics, drug delivery, and treatment of various diseases, including cardiovascular and cerebrovascular diseases. Nanomaterials such as nanozymes have gained success with remarkable therapeutic efficacy due to their stability, formulations, enzyme-mimetic activities, and ability to deliver more than one drug. Moreover, nanozymes can uphold a constant rate of drug release, maintaining a low frequency of dosing to reduce the side effects of drugs. Due to their multifunctional nature, they can be used as targeted delivery vehicles to the damaged brain, arterial, and other tissues to mitigate inflammation and ROS while promoting blood-brain barrier protection, ischemic stroke neurovascular recovery, and neuronal cell survival. In this review article, we have explored the mechanisms and different types of nanozyme-based targeted therapies for several cardiovascular and cerebrovascular diseases, including myocardial infarction, atherosclerosis, and ischemic stroke. We have discussed their enzyme-mimetic catalytic activities, immune-modulatory effects, ROS scavenging abilities, and anti-inflammatory properties. We have also discussed the challenges that slow down the clinical and translational success of these nanozyme-based therapies. Continuing work with integrated and multidisciplinary approaches, these nanozymes may offer potential solutions for cardiovascular and cerebrovascular diseases.